Effectiveness of accommodation and constant resistance training on maximal strength and power in trained athletes - Jalil Ataee; Majid S. Koozehchian; Richard B. Kreider; Li Zuo (PeerJ, 2014)
Accommodation resistance is a training technique that may improve strength and power gains beyond those achieved by traditional free weights. In this method, chains are either added on a free-weight bar and combined with traditional plates or added to the bar as the entire load.Purpose. The aim of the current study was to compare the effectiveness of accommodation and constant resistance training methods during a four-week period on maximal strength and power in trained athletes.Methods. This study was comprised of 24 trained athletes, including 16 trained males [8 Wushu athletes (Kung-Fu) and 8 wrestlers, age: 20.5 ± 2.00 yrs. old]. Participants were initially tested on weight, body circumference, fat percent, upper and lower body maximal strength, determined by the 1-repetition maximum (1RM) test, which determines the greatest amount of weight a person can successfully lift, and upper and lower body power. Participants were equally randomized to either accommodation or constant resistance training groups. Both groups underwent resistance training for a four-week period that consisted of three sessions per week. Multivariate repeated-measures analyses of variance of the data were used to verify significant differences in strength and power between groups. The modified Bonferroni post hoc test was used to compare the obtained results in pre-, mid-, and post test.Results. In the accommodation resistance group, there was a significant difference in lower body maximal strength compared to the constant group (163.12 ± 18.82 kg in the accommodation group vs. 142.25 ± 20.04 kg in the constant group, P = 0.04). No significant differences were found in upper body power, lower body power, and upper body maximal strength between the two groups (P > 0.05).Conclusion. Although there was only a significant difference in lower body maximal strength between groups, accommodation resistance training may induce a physiological training response by improving the strength and power of stabilizing muscle groups required to balance the bar if consistently used over time.